Nano-Medicine Integration: Impact of Recent Breakthroughs in Genetic-Based Diagnosis and Therapyano-Medicine Integration: Impact of Recent Breakthroughs in Genetic-Based Diagnosis and Therapy - Alves, Livia; Souza, Felipe; Muntasir, Muntasir; Naibaho, Netty Maria (Journal of World Future Medicine, Health and Nursing, 2025)
The integration of nanotechnology into medicine has revolutionized genetic-based diagnostics and therapeutic interventions, offering unprecedented precision in disease detection and treatment. Advances in nano-medicine have enabled early-stage disease identification, targeted drug delivery, and personalized medical treatments, particularly in oncology, neurology, and rare genetic disorders. Despite these advancements, challenges such as biocompatibility, scalability, and regulatory approval remain significant barriers to widespread clinical implementation. This study aims to analyze the impact of nano-medicine on genetic-based diagnosis and therapy, assess its effectiveness in enhancing patient outcomes, and identify the obstacles limiting its adoption. A systematic review methodology was employed, analyzing peer-reviewed articles, clinical trial reports, and experimental studies from 2018 to 2024. The findings indicate that nano-medicine significantly improves genetic disease detection accuracy, enhances drug bioavailability, and minimizes adverse side effects through precision-targeted therapies. However, issues such as high development costs, ethical concerns, and long regulatory processes impede rapid integration into mainstream healthcare. This study concludes that nano-medicine represents a paradigm shift in genetic-based medical interventions, requiring further research in bioengineering optimization, regulatory framework standardization, and cost-effective production. Future studies should explore AI-driven nanotechnology applications and their role in improving real-time genetic diagnostics and personalized therapies.